The Birth and the Development of the Idealized Concept of Arcadia in the Late Classical Societies - Corso, Antonio (Actual Problems of Theory and History of Art, 2015)
In the late archaic aristocratic thought the polis begins to be seen from a negative point of view as a milieu dominated by the lowest part of a society. This negative concept becomes very trendy in the 5th century Athenian culture, especially in the second half of the period. Soon after the visual culture reveals that the world far from the life of the community is seen in very positive terms. This phenomenon is appreciated especially thanks to the many representations of Artemis clad in short diploid chiton running in the grove. In the late 5th century BC a new and positive notion of the life far from the city is outlined by Xenophon. Moreover, the visual culture of Greece in late Classical times is flooded with representations of appealing teenage deities in the forest. The location of this paradisiacal environment in Arcadia is given in a picture attributed to Apelles.
Keywords: Arcadia; Phidias; Euripides; Antiphon; Artemis; Xenophon; Praxiteles; Apelles; Anyte of Tegea